Perceptions of primary care physicians about early diagnosis of rheumatoid arthritis and methotrexate monitoring - N., Alrashdi Mousa; M., Alrasheedi S.; A., Alsulmi H.; Majed, Alenazi; Hassan, Daghasi; M., Bedaiwi (International Journal of Advances in Medicine, 2020)
Background: Current guidelines recommend the early recognition and diagnosis of rheumatoid arthritis and treatment with disease-modifying antirheumatic drugs (DMARDs). Methotrexate is the first drug of choice for most patients with rheumatoid arthritis, but this medication has contraindications and side effects that need monitoring. This survey analysis aims to explore the level of knowledge of primary healthcare physicians towards the early detection of rheumatoid arthritis and monitoring treatment with methotrexate. Methods: A self-administered structured questionnaire was distributed to primary healthcare physicians in the region of Riyadh, Saudi Arabia. The survey consists of sections including the demographics of respondents, knowledge about rheumatoid arthritis, and methotrexate. Data were analyzed using SPSS version 22. Results: In total, 249 physicians responded to the survey. Physicians with more years of experience showed a significantly higher level of knowledge about rheumatoid arthritis and methotrexate monitoring (p-value <0.001). The responses of physicians regarding knowledge about the disease were better than their responses about the drug. Conclusions: The knowledge of primary healthcare physicians in Riyadh, Saudi Arabia, is considered satisfactory in regard to rheumatoid arthritis diagnosis, but the level of knowledge about methotrexate requires improvement.